Characterization of apoptotic macrophages in atheromatous tissue of humans and heritable hyperlipidemic rabbits - Kinscherf, Ralf; Kamencic, Huse; Bonaterra, Gabriel; Hou, Dongming; Schiele, Rainer A.; Deigner, Hans-Peter; Metz, Jürgen (Atherosclerosis, 1999)
Apoptotic macrophages are regularly found in atherosclerotic plaques indicating programmed cell death as one of their regulatory controls. The objective of this study was to characterize in more detail apoptotic macrophages in atherosclerotic lesions of humans and heritable hyperlipidemic (HHL) rabbits. Macrophages were immunohistochemically analyzed using antibodies directed against αMβ2-integrins (CD11b/CD18), CD44, major histocompatibility complex (MHC) class I and II, inducible nitric oxide synthase (iNOS), manganese superoxide dismutase (MnSOD), tumor necrosis factor alpha (TNFα), p53, c-jun/AP-1 and rabbit macrophages (RAM-11) and the TUNEL (TdT-mediated dUTP nick end labeling) technique. Colocalization studies of human atherosclerotic carotid and aortic tissue showed apoptotic plaque macrophages also being MnSOD-, αMβ2-integrin-, CD44-, MHC class I- and II-, iNOS-, TNFα- and p53-immunoreactive. Similar results occurred in atherosclerotic aortas of HHL rabbits. Computer-assisted morphometric analyses revealed a positive correlation of the area density of MnSOD-immunoreactive macrophages with those of αMβ2-integrin- and CD44-immunoreactive ones, but not with those of MHC class I- and II- as well as of RAM-11-immunoreactive macrophages. We conclude that apoptotic macrophages located in atherosclerotic vessel wall are activated, antigen-presenting, integrin-expressing and oxidatively stressed cells. Since all these processes have been demonstrated to cause apoptosis of macrophages in vitro, we propose their potency accelerates the susceptibility of the macrophages to programmed cell death in atherosclerotic lesions.